A capability approach to the well-being of informal apprentices and journeypersons in the automotive trade in Ghana - Alla-Mensah, Joyceline (2021)
Informal apprenticeship, although the oldest skills training institution, gained prominence in the education and development policy following the “discovery” of the informal economy in Ghana almost 50 years ago. In the wake of a decline in formal wage employment and high youth unemployment, it has been embraced as an avenue for preparing the youth for work in the informal economy, while serving as an instrument to improve its productivity. On the other hand, the literature suggests apprenticeship is poorly perceived by the youth. Theoretically, informal apprenticeship sits firmly in the growth model of development as its utility is linked to its contribution to poverty reduction and growth. However, poverty is conceived narrowly, in terms of income. Using the capability approach to conceptualise poverty as capability deprivation, this study seeks to understand why young people enrol in apprenticeship, the capabilities they value and the extent of freedom they have to advance their capabilities. The study draws on interviews with informal apprentices, journeypersons, and master craftspersons (MCPs) in the automotive trade in Ghana. Also, other stakeholders such as government officials and representatives of the Ghana National Association of Garages (GNAG) are interviewed. Participants are selected from Kumasi (the capital of the Ashanti Region) and Accra, which is the capital city of Ghana and the Greater Accra Region. The study makes three key contributions to the literature on education and training. First, it brings fresh perspectives to the debate on the vocational aspirations of young people in Africa. A narrative approach adopted helps to understand the structural influences on young people’s choices and the extent to which they engage with these, whilst challenging deficit views about them and informal apprenticeship. Second, the study draws attention to the dimensions of capabilities or well-being freedoms that are valued by informal apprentices and journeypersons. This provides a holistic understanding of the different domains of well-being associated with informal apprenticeship. Also, it helps to focus discussion on the extent to which social arrangements expand the freedoms of apprentices and journeypersons to achieve well-being freedoms. Lastly, this study contributes to the literature on gender in training. By focusing on male and females in the automotive trade in Ghana, gendered experiences are brought to the fore. The findings show that contrary to the often-structural way in which females’ participation in male-dominated trades is perceived, females are critical of gender norms. On the other hand, conditions of training and an enabling environment that supports their smooth transition from training to self-employment need attention.